PENDIDIKAN KEWIRAUSAHAAN DI PONDOK PESANTREN SIDOGIRI PASURUAN - Chusnul Chotimah (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
This research discuss the entrepreneurship models and its teaching strategy in Sidogiri Islamic boarding school Pasuruan through qualitative method. The finding shows that (1) entrepreneurship values are integrated as religious activities in which any economic activities is part it and intended for God; (2) under the control of boarding school head, the education proses on entrepreneurship is giving the student attempt to organized economic sector in the boarding school.